Structure and function of oncogene-transfected immortal cells - Kavsan, V.M.; Kulagova, T.A.; Kuznetsova, T.A.; Semenkova, G.N.; Stepanenko, A.A.; Vassetzky, Y.S. (Вiopolymers and Cell, 2014)
Previously we have characterized a new oncogene CHI3L1, overexpressed in the glioblastoma and the malignant 293_CHI3L1 cells, stably producing the CHI3L1 angiogenic oncoprotein. The 293_CHI3L1 cells proliferated faster and acquired a higher ability for anchorage-independent growth. Here, we report the atomic force microscopy data and functional characteristics of these cells. The constitutive CHI3L1 expression leads to the increased resistance to the damages by oxidative substances and promotes the chromosome instability in the 293 cells. According to the data of the last clinical investigations, anti-cancer therapy should be targeted not at the individual genes, but at the pathological effects they caused. We propose a complex treatment of gliomas including multi-target inhibitors, which can be delivered to the brain tumor by a specific nanoparticle vector. Раніше нами охарактеризовано новий онкоген CHI3L1, який суперекспресується в гліобластомі та злоякісних клітинах 293_CHI3L1, щo стабільно продукують ангіогенний онкобілок CHI3L1. Клітини 293_CHI3L1 проліферують швидше і набувають більшої здатності до незалежного від основи росту. Наведено дані атомносилової мікроскопії та функціональні характеристики зазначених клітин. Конститутивна експресія CHI3L1 підвищує стійкість до пошкоджень речовинами-окиснювачами і сприяє нестабільності хромосом у клітинах 293. За даними останніх клінічних випробувань, протиракова терапія повинна бути націлена не на індивідуальні гени, а на спричинені ними патологічні ефекти. Ми пропонуємо комплексне лікування гліом із залученням багатомішенних інгібіторів, які можна доствляти до пухлин головного мозку специфічним вектором на основі наночасток. Ранее нами охарактеризован новый онкоген CHI3L1, суперэкспрессирующийся в глиобластоме и злокачественных клетках 293_CHI3L1, стабильно продуцирующих ангиогенный онкобелок CHI3L1. Клетки 293_CHI3L1 пролиферируют быстрее и приобретают большую способность к независимому от подложки росту. Приведены данные атомно-силовой микроскопии и функциональные характеристики указанных клеток. Конститутивная экспрессия CHI3L1 повышает устойчивость к повреждениям веществами-окислителями и способствует нестабильности хромосом в клетках 293. По данным последних клинических испытаний, противораковая терапия должна быть нацелена не на индивидуальные гены, а на вызываемые ими патологические эффекты. Мы предлагаем комплексное лечение глиом с привлечением мультимишенных ингибиторов, которые можно доставлять к опухолям головного мозга специфическим вектором на основе наночастиц.